Repositioned Natural Compounds and Nanoformulations: A Promising Combination to Counteract Cell Damage and Inflammation in Respiratory Viral Infections - Alessia Mariano; Irene Bigioni; Magda Marchetti; Anna Scotto d’Abusco; Fabiana Superti (Molecules, 2023)
Respiratory viral diseases are among the most important causes of disability, morbidity, and death worldwide. Due to the limited efficacy or side effects of many current therapies and the increase in antiviral-resistant viral strains, the need to find new compounds to counteract these infections is growing. Since the development of new drugs is a time-consuming and expensive process, numerous studies have focused on the reuse of commercially available compounds, such as natural molecules with therapeutic properties. This phenomenon is generally called drug repurposing or repositioning and represents a valid emerging strategy in the drug discovery field. Unfortunately, the use of natural compounds in therapy has some limitations, due to their poor kinetic performance and consequently reduced therapeutic effect. The advent of nanotechnology in biomedicine has allowed this limitation to be overcome, showing that natural compounds in nanoform may represent a promising strategy against respiratory viral infections. In this narrative review, the beneficial effects of some promising natural molecules, curcumin, resveratrol, quercetin, and vitamin C, which have been already studied both in native form and in nanoform, against respiratory viral infections are presented and discussed. The review focuses on the ability of these natural compounds, analyzed in in vitro and in vivo studies, to counteract inflammation and cellular damage induced by viral infection and provide scientific evidence of the benefits of nanoformulations in increasing the therapeutic potential of these molecules.